STUDENTS’ ATTRIBUTIONS ON THEIR ENGLISH SPEAKING ENHANCEMENT - Mali, Yustinus (Indonesian Journal of Applied Linguistics, 2015)
Abstract: Attribution refers to explanations and reasons that people provide for progress, achievement, and even failure towards something they have experienced, particularly in their language learning. This study aimed to investigate the attributions that students had for their English-speaking enhancement. The participants of the study were eighteen students at Sekolah Tinggi Pariwisata Ambarukmo Yogyakarta (STIPRAM). Open-ended questionnaire and interview were used as the instruments to collect the data. On the questionnaire, the participants were specifically asked to provide written responses to three statements, while in the interview process, the researcher involved three participants to provide further clarification toward their written responses on the questionnaire. The data analysis revealed that a clear purpose of doing particular English speaking activities, strategy, and the positive motivation/encouragement from friends as well as from the teacher became the major students’ attributions on their English-speaking enhancement. Besides, this study would seem to indicate that a teacher took an essential role in the enhancement of the students’ English speaking skill. Eventually, this study proposed some pedagogical implications for the development of teaching and learning in English speaking classes specifically in Indonesian context.